USULAN PENERAPAN ISAK 335 DALAM PENYAJIAN LAPORAN KEUANGAN YAYASAN KESEJAHTERAAN KARYAWAN DAN PENSIUNAN BANK X - Syamsulhadi, Luthfi; Khairunnisa, Hera; Muhammad Zairin, Gentiga (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2025)
This study aims to analyze the accounting cycle and SWOT in the accounting cycle applied at YKKP Bank X, as well as to analyze the presentation of financial statements as of January 31, 2024 made by YKKP Bank X and provide suggestions regarding the presentation of YKKP X's financial statements for 2024 in accordance with ISAK 335. This study uses a qualitative approach with a case study research method. The data sources used are primary data and secondary data. The data analysis techniques used in this study are data reduction, data display, and drawing conclusions. The results of the study obtained are that the accounting cycle applied at YKKP Bank X is in accordance with SAK ETAP. The application of the SWOT matrix related to the results of the SWOT analysis in the accounting cycle applied at YKKP Bank X produces the Strengths-Threats (ST) strategy and the Weaknesses-Threats (WT) strategy. This study also presents the financial statements of YKKP Bank X for 2024 which have been adjusted to ISAK 335 which consists of a statement of financial position, a statement of comprehensive income, a statement of changes in net assets, a cash flow statement, and notes to the financial statements